Rapid evolution of a voltage-gated sodium channel gene in a lineage of electric fish leads to a persistent sodium current - Thompson, Ammon (PLoS Biol, 2018)
Most weakly electric fish navigate and communicate by sensing electric signals generated by their muscle-derived electric organs. Adults of one lineage (Apteronotidae), which discharge their electric organs in excess of 1 kHz, instead have an electric organ derived from the axons of specialized spinal neurons (electromotorneurons [EMNs]). EMNs fire spontaneously and are the fastest-firing neurons known. This biophysically extreme phenotype depends upon a persistent sodium current, the molecular underpinnings of which remain unknown. We show that a skeletal muscle–specific sodium channel gene duplicated in this lineage and, within approximately 2 million years, began expressing in the spinal cord, a novel site of expression for this isoform. Concurrently, amino acid replacements that cause a persistent sodium current accumulated in the regions of the channel underlying inactivation. Therefore, a novel adaptation allowing extreme neuronal firing arose from the duplication, change in expression, and rapid sequence evolution of a muscle-expressing sodium channel gene.